A networking laboratory using an integrated mixture of physical equipment and simulators. Issue 5 (2nd May 2017) - Chan, Ka C.; Haythorne, Sean
Abstract: This article presents the design and development of a networking laboratory that integrates a combination of physical networking equipment with the open source GNS3 network simulators for on‐campus, blended‐learning, and potentially online delivery of networking classes. This transformative work has resulted in a significant increase in laboratory capacity, thus reducing the need for repeating classes. The integrated platform offers students both hands‐on experience using real equipment, and the convenience of easy setup and reconfiguration using simulators. An example practical exercise in setting up an OSPF/BGP network is presented to illustrate the experimental design before and after the integration of GNS3 simulators. In summary, we describe the infrastructure, the integrated platform and systems, network design and experiment design; and the learning and teaching experiences of using GNS3 in classes.